Isochronous Gaussian Sampling and its applying to the Falcon Signature Scheme: Fìz.-mat. model. ìnf. tehnol. 2021, 32:106-110 - Derevianko, Yaroslav; Baklykov, Oleksandr (PHYSICO-MATHEMATICAL MODELLING AND INFORMATIONAL TECHNOLOGIES, 2021)
This paper describes a block framework for generating discrete Gaussian components with arbitrary center and standard deviation. Simplicity makes it easy to implement secure, portable, effective, and time-resistant. This sampler is a good candidate for any sample analysis. Most importantly, it was recently introduced into the Falcon Signature Scheme. Gaussian sampling over integers is a central element of algebraic lattice cryptography, which is difficult to perform efficiently and safely. Given the vast number of uses of sampling processes, it is important to select Gaussian samplers that are effective provably secure, resistant to transient attacks, and generally easy to implement. Sampling with other distributions, other than Gaussian, is yet an open question. References Prest, T. (2015). Gaussian Sampling in Lattice-Based Cryptography. Theses, École Normale Supérieure. Howe, J., Prest, T., Ricosset, T., Ross, R. (2019). Isochronous Gaussian Sampling: From Inception to Implementation. (2020).Post-Quantum Cryptography. Round 3 Submissions. Fouque, P.-A., Hoffstein, J., Kirchner, P., Lyubashevsky, V., Pornin, T., Prest, T., Ricosset, T., Seiler, G. (2020). William Whyte, Zhenfei Zhang. Falcon: Fast-Fourier Lattice-based Compact Signatures over NTRU Specifications v1.2.